A sublimação para além da arte - Albuquerque, Mauro Reis (2018)
The research came to be from the interest in the field of intersection between psychoanalysis and art, and from the perception of an intimate association between the concept of sublimation and the work with art. The starting question that appears from there is described as “what are the mismatches between sublimation and art?” The research is orientated by the general objective set as to examine the limits in the relation made between art and sublimation, from which three specific objectives are extracted, which are to discuss how to idealization process affects the sublimation and the artistic creation, to investigate the specificity of the artistic creation from others creative processes and to draw aspects of the sublimation not related to art. In order to achieve it, the Freudian work was walked through the points where the author elaborated on the concepts of idealization and sublimation, from where aspects about drive, identification and repression were also extracted. Such efforts also led to the case study of Leonardo da Vinci, which made possible to discuss these concepts in a concrete fashion and together with the interpretation from Jacques Lacan and Orlando Cruxen. From this point, the seventh seminar of Lacan was took as a field in which the research advanced, considering it as the most utilized source of the lacanian discussion of the sublimation concept. Through these efforts, aspects of the satisfaction of the drive in its relation with the Law instance and the way the ideals are formed throughout the psychic constitution were extracted, as well as its role in the sublimation process. Certain organization is perceived between the processes of idealization and sublimation, whose relation is distinguished in the works of Freud and Lacan